EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN THINK – TALK - WRITE TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 3 MAGELANG - Erin Setiyaningrum; Istiqomah Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2015)
The aim of this research is to know the effectivity of using Think-Talk-Write (TTW) type in cooperative learning model in comparison with conventional learning model toward the mathematics learning achievement of VII grade students in SMP 3 Magelang in the year of 2013/2014. The populations in this research are the students of VIIA, VIIB, VIIC, VIID, VIIE, VIIF, VIIG, and VIIH of SMP 3 Magelang. The samples in this research are the students of VIIA and VIID. The technique to take sample used cluster random sampling technique and done by class lottery. The data is analyzed with one party t test that is right parties to examine the hypothesis. The significant level of one party t test is 5%. The prerequisite analysis which is normality and homogeneity has been done previously. Building on the prerequisite test of t test, it is known that the data is normal and homogeny. With the result of that, the hypothesis test by t test can be done. From the description of the learning achievement value, the average of class experiment value ( Â = 82,188) higher that control class value ( Â = 76,25). The result of t test shows that tcount > ttabel (2,060 > 1,645) which is mean that H0 is refused and Ha is accepted. The conclusion of this research is mathematics learning using Think-Talk-Write (TTW) type in cooperative learning model is more effective than convensional learning model toward the mathematics learning achievement of VII grade students in SMP 3 Magelang in the year of 2013/2014.